Bone marrow mesenchymal stem cells are abnormal in multiple myeloma: Myeloma - Corre, J; Mahtouk, K; Attal, M; Gadelorge, M; Huynh, A; Fleury-Cappellesso, S; Danho, C; Laharrague, P; Klein, B; Rème, T; Bourin, P (Leukemia, 2007)
Recent literature suggested that cells of the microenvironment of tumors could be abnormal as well. To address this hypothesis in multiple myeloma (MM), we studied bone marrow mesenchymal stem cells (BMMSCs), the only long-lived cells of the bone marrow microenvironment, by gene expression profiling and phenotypic and functional studies in three groups of individuals: patients with MM, patients with monoclonal gamopathy of undefined significance (MGUS) and healthy age-matched subjects. Gene expression profile independently classified the BMMSCs of these individuals in a normal and in an MM group. MGUS BMMSCs were interspersed between these two groups. Among the 145 distinct genes differentially expressed in MM and normal BMMSCs, 46% may account for a tumor-microenvironment cross-talk. Known soluble factors implicated in MM pathophysiologic features (i.e. IL (interleukin)-6, DKK1) were revealed and new ones were found which are involved in angiogenesis, osteogenic differentiation or tumor growth. In particular, GDF15 was found to induce dose-dependent growth of MOLP-6, a stromal cell-dependent myeloma cell line. Functionally, MM BMMSCs induced an overgrowth of MOLP-6, and their capacity to differentiate into an osteoblastic lineage was impaired. Thus, MM BMMSCs are abnormal and could create a very efficient niche to support the survival and proliferation of the myeloma cells.